The Efforts to Improve the Achievement of Controlled DM Patient Treatment in the Prolanis Program at Jasinga Community Health Center - Enrico Adhitya Rinaldi; Erlina Puspitaloka Mahadewi; Ratna Sari; Salma Nabilah Rafifah; Lisdayanti NA Hi Nur; Vita Emilya; Azzahra Inda Latifan (International Journal of Health and Pharmaceutical (IJHP), 2026)
The aim of this study is to prevent uncontrolled diabetes can lead to various chronic complications, such as coronary heart disease, stroke, kidney failure, neuropathy, and blindness. These conditions not only reduce the patient's quality of life but also increase morbidity and mortality rates, and healthcare costs. As a promotive and preventive effort, the Social Security Administering Agency (BPJS Kesehatan) in Indonesia, has developed the Chronic Disease Management Program (Prolanis), one of which is aimed at people with type 2 diabetes. This program is implemented in primary healthcare facilities (FKTP), including community health centers (Puskesmas), with the aim of improving patients' quality of life through continuous treatment, health education, regular physical activity, and regular clinical monitoring. Prolanis consists of six main components: medical consultations, group education, reminders via SMS gateway, home visits, club activities such as group exercise, and monitoring of patient health status. Research method of this study used a descriptive observational design with a cross-sectional approach and was conducted at the Jasinga Community Health Center from August to September 2025. The subjects were all diabetes mellitus patients registered in the Prolanis program. Result data distribution of patients at Jasinga 38,1% controlled and 61,9% uncontrolled despite these limitations, this study has important implications. From a primary healthcare perspective, Jasinga Health Center can utilize simple educational media such as pamphlets and control cards as a means of patient monitoring. However, this strategy should be complemented by additional interventions such as home visits, the establishment of digital communication groups, and increasing family participation.